2022
DOI: 10.1039/d2tc01834a
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystalline-like indium tin oxide thin films prepared by plasma enhanced atomic layer deposition

Abstract: In this study, indium tin oxide (ITO) thin films are prepared by plasma enhanced atomic layer deposition (PEALD) using alternating exposures to cyclopentadienyl indium and oxygen plasma for indium oxide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The XPS confirmed that the indium and tin atoms bonded to oxygen and presence of oxygen vacancies in thin films. Hsu et al 99 prepared ITO thin films on a glass substrate using plasma‐enhanced atomic layer deposition (PEALD). XPS results confirmed the successful incorporation of Sn into In 2 O 3 .…”
Section: Ito Thin Film Properties and Preparation Dependenciesmentioning
confidence: 99%
“…The XPS confirmed that the indium and tin atoms bonded to oxygen and presence of oxygen vacancies in thin films. Hsu et al 99 prepared ITO thin films on a glass substrate using plasma‐enhanced atomic layer deposition (PEALD). XPS results confirmed the successful incorporation of Sn into In 2 O 3 .…”
Section: Ito Thin Film Properties and Preparation Dependenciesmentioning
confidence: 99%
“…Based on their favorable electrical (o10 À4 O cm), optical (490%), and chemical stability properties, indium tin oxide (ITO) thin films have been used as transparent electrodes for electronic devices. [1][2][3][4][5] However, the relatively high sheet resistance and brittleness of ITO thin films are critical drawbacks for their application in advanced flexible electronics. [6][7][8] Recently, oxide/metal/oxide thin films have been extensively studied as alternative transparent electrodes owing to their outstanding performance, such as low sheet resistance, enhanced flexibility, and roll-to-roll process compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…As a scattered and rare element, indium (In(III)) is extremely rare on earth and often occurs in association with other metal ores. [1] In(III) and its compounds exhibited strong light permeability and electrical conductivity for the fabrication of indium tin oxide (ITO) coating, [2] semiconductors. [3] and infrared photodetectors.…”
Section: Introductionmentioning
confidence: 99%